-2(x-3)=5(2x+5

Simple and best practice solution for -2(x-3)=5(2x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-3)=5(2x+5 equation:



-2(x-3)=5(2x+5
We move all terms to the left:
-2(x-3)-(5(2x+5)=0
We multiply parentheses
-2x-(5(2x+5)+6=0

See similar equations:

| 3(2y-7)=y-1 | | 8.4=4.9t^2+3t | | 1/7y+1/8=9/56 | | 5/4(a-8)=2-3 | | 8(n+3)=2(n-3) | | .9x=13x | | e×12=30.00 | | 33x+295=39x+295 | | 3x2=25x+88 | | x-1-5=4x-6+3 | | x12x+53=213 | | -3(2r+7)=4 | | 3x+4=-7+9 | | 9x+0.6=9.6 | | 6(5-x)+x=-20 | | 3x+8+3x-5=40 | | 8(1-2x)-4x=168 | | 5(r-2)=3(2r-4) | | 7u-(7-u)2=1 | | 4x+0.4=12.4 | | -4(6m-4)=-14+6m | | 29x-6=10x-2+108 | | (x)(14x)=350 | | 3(8+5a)+5a=36+8a | | 2n+17=n | | f+3π=12π | | (8+y)5+(-8y)=19 | | -21-8x=-5-5(x+8) | | 5-2x.X=3 | | 1/3x+5/3x=4(9x-68) | | -5x+18=-(8x+3) | | 21+5+0x=0 |

Equations solver categories